Statin associated adverse reactions in Latin America: a scoping review (2021)
Objectives We aim to describe the frequency and type of adverse drug reactions (ADRs) in patients on statins in published studies from Latin American (LATAM) countries. Design Scoping review. Methods A literature search was conducted in three databases (PubMed, EMBASE and LILACS) in addition to a manual search in relevant journals from LATAM universities or medical societies. A snowballing technique was used to identify further references. Randomised controlled trials (RCTs) and observational studies between 2000 and 2020 were included. Studies were considered eligible if they included adults on statin therapy from LATAM and reported data on ADRs. Data on ADRs were abstracted and presented by study design. Results Out of 8076 articles, a total of 20 studies were included (7 RCTs and 13 observational studies). We identified three head-to-head statin RCTs, two statinversus-policosanol RCTs and only two placebo-controlled trials. The statin-related ADRs frequency ranged from 0% to 35.1% in RCTs and 0% to 28.4% in observational studies. The most common ADRs were muscle-related events including myalgia and elevated creatine phosphokinase. Other reported ADRs were gastrointestinal symptoms, headache and altered fasting plasma glucose.